2023
DOI: 10.3389/fpubh.2023.1198439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green space on physical activity and body weight status among Chinese adults: a systematic review

Abstract: BackgroundGreen space may provide many benefits to residents’ health behaviors and body weight status, but the evidence is still relatively scattered among Chinese adults. The purpose of this study was to review the scientific evidence on the effects of green space on physical activity (PA) and body weight status among Chinese adults.MethodsA keyword and reference search was conducted in Pubmed, Web of Science, MEDLINE, and PsycINFO. Studies examining the associations between green space and PA, body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…In our comprehensive review of 26 studies, 19 of them revealed a positive correlation between street greenery and various aspects of active travel, including the duration and distance of travel, participation probability, frequency, and satisfaction. These findings align with prior research, emphasizing the positive impact of green spaces on physical activity among Chinese adults (50) and associating street greenery with increased active commuting (51). However, inconsistencies surfaced across different variables, primarily attributed to variations in measurement methods.…”
Section: Discussionsupporting
confidence: 90%
“…In our comprehensive review of 26 studies, 19 of them revealed a positive correlation between street greenery and various aspects of active travel, including the duration and distance of travel, participation probability, frequency, and satisfaction. These findings align with prior research, emphasizing the positive impact of green spaces on physical activity among Chinese adults (50) and associating street greenery with increased active commuting (51). However, inconsistencies surfaced across different variables, primarily attributed to variations in measurement methods.…”
Section: Discussionsupporting
confidence: 90%
“…Higher evaluation scores indicate higher quality of the included literature. The strength of the scientific evidence was measured using study quality assessment, however, the inclusion of research was not taken into consideration [ 27 , 28 ]. The specific criteria and results of the literature quality evaluation can be found in Supplement 1 .…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence that supports the health benefits of exposure to nature [1][2][3][4][5][6][7][8][9][10][11][12][13], and engaging in nature-based activities [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Allied health professionals (AHPs) can play an important role in improving people's access to and use of nature, by working with individual patients/clients, communities and from a broader public health perspective, including advocacy for and input into the design of public natural environments.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been a shift away from healthcare settings in nature, there has been an increase in research into the benefits of exposure to nature (e.g. green [1][2][3][4][5][6][7][8][9][10][11][12][13] and blue spaces [2,10,13]), and nature-based activities to improve health and wellbeing [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Allied health professionals are well placed to integrate NBAs -by encompassing outdoor and indoor nature-based activities which may be recommended or directly engaged in with the patient/ client, and advocacy for or the provision of improvements to natural spaces -into their practice.…”
Section: Introductionmentioning
confidence: 99%